A Bibliometric Overview of Prabandhan: Indian Journal of Management between 2011 and 2021 - Ludhani, Kamal K.; Kumar, Sanjay; Panda, Saroja Kumar (Prabandhan: Indian Journal of Management, 2023)
This study used bibliometric analysis to examine Prabandhan : Indian Journal of Management’s recent 10 - year publications. The study's goal was to present a comprehensive summary of the journal's major influences. This analysis covered the journal's publication and citation structure; the most cited articles; and top authors, institutions, and nations. Using VOSviewer and Gephi Software, we created a graphical mapping of bibliographic material. With this software, we performed keyword analysis and bibliographic coupling analysis. As a result of this analysis, nine major research themes emerged: (a) higher education and skills, (b) job satisfaction and employee performance, (c) stress management and women, (d) corporate social responsibility, (e) innovation and strategy, (f) emotional intelligence, (g) entrepreneurship, (h) green management, (i) technology and small & medium enterprises.